ANALISIS SISTEM PENGENDALIAN INTERNAL PEMERINTAH ATAS AKUNTABILITAS PENGELOLAAN KEUANGAN DANA DESA DI DESA TAWALIAN TIMUR KABUPATEN MAMASA - Herlinda Anastasya; Suzy Noviyanti (ITB AAS INDONESIA, 2023)
This study aims to find out how the implementation of the government's internal control system for the accountability of village fund financial management in East Tawalian Village consists of control environment, risk assessment, control activities, information and communication, and monitoring. This research is a qualitative descriptive study through direct interviews conducted with 5 people namely the Village Head, Village Secretary, Village Treasurer, Village Consultative Body (BPD), and several East Tawalian Village Officials. The results of research conducted in East Tawalian Village indicated that SPIP had not been fully implemented because the implementation of guidance on village officials had not been effective and there was a lack of accountability from the village government in managing village funds. In the process of managing village funds there are still obstacles, namely delays in the process of activities carried out in the village where the work carried out is not done on time so that it affects the preparation of SPJ and has an impact on accountability and accountability for managing village funds and physical control over assets related to BUMDes has not been carried out by the Government East Tawalian Village.